2001
DOI: 10.1054/bjoc.2001.1946
|View full text |Cite
|
Sign up to set email alerts
|

Adult height and risk of breast cancer: a possible effect of early nutrition

Abstract: The relationship of breast cancer to early reproductive development and height suggests that fetal and childhood nutrition may be important in its aetiology. Caloric restriction sufficient to reduce adult height may reduce breast cancer risk. During World War II (WWII) there was a marked reduction in average caloric intake in Norway that resulted in greater nutritional diversity. We hypothesized that a positive association between height and risk of breast cancer would be stronger among women who were born dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 26 publications
2
14
0
Order By: Relevance
“…The absence of association in our study between height and premenopausal breast cancer risk may be attributed to small numbers in this category or to a limited height range in our cohort, with few tall women (12). Height is a biomarker of nutrition and growth factors in childhood (13)(14)(15)(16). Although the interest of these variables was recently discussed (6), leg length and sitting height are considered more closely associated to growth hormone exposure than height, respectively, before and after menarche (1,10).…”
Section: Discussionmentioning
confidence: 66%
“…The absence of association in our study between height and premenopausal breast cancer risk may be attributed to small numbers in this category or to a limited height range in our cohort, with few tall women (12). Height is a biomarker of nutrition and growth factors in childhood (13)(14)(15)(16). Although the interest of these variables was recently discussed (6), leg length and sitting height are considered more closely associated to growth hormone exposure than height, respectively, before and after menarche (1,10).…”
Section: Discussionmentioning
confidence: 66%
“…Energy restriction during the growth years is associated with reduced adult stature and a reduced number of breast tissue cells, which affects the risk of breast cancer (De Waard and Trichopoulos, 1988). Lund Nilsen and Vatten (2001) found supporting results in a recent Norwegian cohort study. A positive association was observed between adult height and breast cancer, for women born during a period of nutritional diversity (World War II).…”
Section: Discussionmentioning
confidence: 67%
“…Other ecological studies have also underlined the possible importance of food intake (Doll and Peto, 1981;De Waard and Trichopoulos, 1988;Potishman et al, 1998). Furthermore, the observed positive association between body height and breast cancer is attributed to dietary conditions in early life (Tretli, 1989;Vatten et al, 1992; Van der Brandt et al, 1997;Lund Nilsen and Vatten, 2001). …”
mentioning
confidence: 98%
“…Several studies have used the adverse circumstances during World War II to explore this issue. In Norway, it seemed that the decrease in caloric intake during the war, due to rationing, resulted in decreased breast cancer risk in women who were born or were peripubertal at that time (8)(9)(10)(11). However, we showed that a fierce famine in The Netherlands during the last year of World War II has resulted in increased risk of breast cancer, particularly if exposure was during childhood (12).…”
Section: Introductionmentioning
confidence: 60%